RETRACTED: Pengembangan Aplikasi Berbasis Android untuk Media Membaca Permulaan Siswa Kelas I Sekolah Dasar - Erlina, Tiara; Iswara, Prana Dwija (Universitas Negeri Malang, 2023)
Following a rigorous, carefully concerns and considered review of the article published in Sekolah Dasar: Kajian Teori dan Praktik Pendidikan to article entitled “PENGEMBANGAN APLIKASI BERBASIS ANDROID UNTUK MEDIA MEMBACA PERMULAAN SISWA SD KELAS I” Vol. 32, No. 1, May 2023, URL: https://journal2.um.ac.id/index.php/sd/article/view/37480This paper has been found to be in violation of the Sekolah Dasar: Kajian Teori dan Praktik Pendidikans' publication principles and has been retracted.The article contained redundant material, the editor investigated and found that the paper published in Attadib: Journal of Elementary Education, Vol. 7, No. 2, June 2023, URL: https://jurnalfai-uikabogor.org/index.php/attadib/article/view/1930The document and its content has been removed from Jurnal Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, and reasonable effort should be made to remove all references to this article.